Doing business in Myanmar: Dressing up the bride - Trivedi, Ma Cherry (Institutional Knowledge at Singapore Management University, 2018)
Dressing up the bride. As one of the untapped frontiers of newly emerging markets, Myanmar is rich in natural resources, underpopulated but with growing purchasing power, and an easy place to do business. From the outside, the country is very inviting, and there is considerable interest in doing business in Myanmar today. But internally, we have several pockets of obstacles.